Performance Improvement for Hybrid L-band Remote Erbium Doped Fiber Amplifier/Raman using Phase Modulator - Nelidya Md. Yusoff; A. H. Sulaiman; Sumiaty Ambran; Azura Hamzah; M. A. Mahdi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
We have demonstrated the performance improvement of L-band hybrid remote Erbium-doped fiber amplifier by introducing a phase modulator to suppress the stimulated Brilloiun scattering (SBS) effect in the transmission. The transmission gain has improved by 12.65dB while the noise figure has reduced by 47.1dB when 0dBm signal power is generated at 1590.05nm wavelength. Furthermore, the optical signal-to-noise ratio has improved from 7.81dB to 29.72dB when the signal power is varied from -30dBm to 0dBm. By implementing a phase modulator to the input signal somehow able to produce better performance regarding gain, noise figure and optical signal-to-noise ratio, especially at the higher signal power as the gain, has been transferred to the Stokes signal and the amplified signal.